Oxidative passivation of metal halide perovskites - Godding, J; Ramadan, A; Lin, Y; Schutt, K; Snaith, H; Wenger, B (Cell Press, 2019)
Metal halide perovskites have demonstrated extraordinary potential as materials for next-generation optoelectronics including photovoltaics and light-emitting diodes. Nevertheless, our understanding of this material is still far from complete. One remaining puzzle is the phenomenon of perovskite “photo-brightening”: the increase in photoluminescence during exposure to light in an ambient atmosphere. Here, we propose a comprehensive mechanism for the reactivity of the archetypal perovskite, MAPbI3, in ambient conditions. We establish the formation of lead-oxygen bonds by hydrogen peroxide as the key factor leading to perovskite photo-brightening. We demonstrate that hydrogen peroxide can be applied directly as an effective “post-treatment” to emulate the process and substantially improve photoluminescence quantum efficiencies. Finally, we show that the treatment can be incorporated into photovoltaic devices to give a 50 mV increase in open-circuit voltage, delivering high 19.2% steady-state power conversion efficiencies for inverted perovskite solar cells of the mixed halide, mixed cation perovskite FA0.83Cs0.17Pb(I0.9Br0.1)3.